Contribuiç\~oes à nova agenda urbana: O relatório do concidades para a Conferência Habitat III - Bárbara Marguti; Carlos Vinícus da Silva Pinto; César Buno Favar\~ao; Ernesto Pereira Galindo; Letícia B. Klug; Marco Aurélio Costa; Thadeu Q. Magalh\~aes; Roberta Amanajás Monteiro; Rodrigo Luís Comini Curi; Sara Rebello Tavares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Every 20 years, the United Nations Organization (UN) promotes the Conference on Housing and Sustainable Urban Development (Habitat) to discuss the problems of housing and urban development and to sign international commitments that favor the existence and production of settlements Human resources. In preparation for the third edition of Habitat, the UN proposed the production of national reports from Member States to guide negotiations on the new global urban agenda. At the invitation of the National Council of Cities (ConCidades), Ipea was responsible for drafting the Brazilian Report for Habitat III. In this context, the following text discusses the main themes incorporated in this process of discussion / construction of the New Brazilian Urban Agenda.
Keywords: O38; R28; O15; 330; New Urban Agenda; Conference Habitat III; right to the city; sustainable urban development